An Outbreak of Cholera Associated with an Unprotected Well in Parbatia, Orissa, Eastern India - Das, Amitav; Manickam, P; Hutin, Yvan; Pal, BB; Chhotray, GP; Kar, SK; Gupte, MD (Journal of Health, Population and Nutrition, 2009)
In November 2003, an outbreak (41 cases; attack rate-4.3%; no deaths) of severe diarrhoea was reported from a village in Orissa, eastern India. Thirteen of these cases were hospitalized. A matched case-control study was conducted to identify the possible exposure variables. Since all wells were heavily chlorinated immediately after the outbreak, water samples were not tested. The cases were managed symptomatically. Descriptive epidemiology suggested clustering of cases around one public well. Vibrio cholerae El Tor O1, serotype Ogawa was isolated from four of six rectal swabs. The water from the public well was associated with the outbreak (matched odds ratio: 12; 95% confidence interval 1.2-44.1). On the basis of these conclusions, access to the well was barred immediately, and it was protected. This investigation highlighted the broader use of field epidemiology methods to implement public-health actions guided by epidemiologic data to control a cholera epidemic. J Health Popul Nutr 2009 Oct; 27(5):646-651